2022
DOI: 10.25257/fe.2022.3.99-109
|View full text |Cite
|
Sign up to set email alerts
|

Algorithm of actions of fire service to extend high-pressure hoses when extinguishing a fire on the railway

Abstract: Purpose. Rail transport is one of the safest types of transportation, however, train accidents and catastrophes entail loss of life and significant property damage. A topical issue is the uninterrupted fire suppressant supply in case of fires on the railway. The authors present the results of an experiment on the development of a connecting device prototype to extend high-pressure hoses during firefighting. Methods. The authors have applied a comprehensive analysis of situational factors on the basis of practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Practical implementation of proposals for determining the strength of PFHs and improving their design and production may be the best confirmation of the feasibility of taking into account the extension of PFH during fire extinguishing. Thus, the uninterrupted supply of extinguishing agents during fires on the railway due to the development of a prototype connecting device for lengthening high-pressure hoses is considered in [10]. The authors found that the lengthening of the hoses affects the effectiveness of their use in hard-toreach places.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Practical implementation of proposals for determining the strength of PFHs and improving their design and production may be the best confirmation of the feasibility of taking into account the extension of PFH during fire extinguishing. Thus, the uninterrupted supply of extinguishing agents during fires on the railway due to the development of a prototype connecting device for lengthening high-pressure hoses is considered in [10]. The authors found that the lengthening of the hoses affects the effectiveness of their use in hard-toreach places.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The authors found that the lengthening of the hoses affects the effectiveness of their use in hard-toreach places. Despite the fact that the proposals for the use of hoses provided in [10] can reduce the consumption of extinguishing agent, the difficulty of using equipment with high liquid pressure values remains. Moreover, sometimes the laying of the hose line is further complicated in places that are difficult to reach by a fire truck.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%